Pengaruh Faktor-Faktor Fundamental Terhadap Nilai Perusahaan - Usemahu, Rasni Hanipa (Journal of Applied Accounting, 2024)
The purpose of this research to determine the influence of investment decisions, funding decisions and profitability on company value. Case studies of real estate and property companies listed on the IDX in 2019-2022"The type of data used is secondary data Financial reports of Real Estate and Property companies that go public on the Indonesia Stock Exchange (BEI) for the period 2019 to 2022. Data obtained from IDX website: www.idx.co.id, the sample was determined using a purposive sampling method, there were approximately 45 Real Estate and Property companies. In the existing population, the sample that meets the specified criteria is 23 companiesthe results of data analysis regarding the influence of investment decisions, funding decisions and profitability on company value in real estate and property companies listed on the Indonesia Stock Exchange (BEI) for the period 2019 – 2022. The conclusion is that investment decisions, funding decisions and profitability simultaneously influence company value in real estate and property. The F value = 7.206 with a significance of 0.000 is smaller than the expected significance level of 0.05 so that Ha is accepted and Ho is rejected. Keywords: Investment decisions, financing decisions and profitability